How sweet it is [large type] - Christenson, Andrea (Christenson, Andrea. Fox Family, 2025)
"Robin Fox is living out her dreams working in a gourmet bakery in Paris. She thought she'd live there forever, but when her relationship with her boss sours, those dreams crumble. She finds herself back home in Deep Haven, Minnesota, caring for her grandparents' rundown bakery while they're away. But she vows that when they return in six weeks, she'll trade this ordinary life for the one she left behind. Sammy Johnson has never gotten traction in any area of his life. This hasn't improved in the almost two years since the accident which nearly killed him. Although his heart is still beating, it contains little passion for the life he's living in Deep Haven. But that begins to change when he offers to help his former high school friend, Robin. Working together to keep Fox Bakery from going under, they find more than friendship is simmering between them. But when the six weeks are up, will Robin follow her old dreams back to the glamor of Paris or will she discover how sweet it is to be loved in Deep Haven?"--